A Systematic Literature Review on User Interface Design for Web Applications - Shamat, Nur Atikah; Sulaiman, Shahida; Sinpang, Jacline Sudah (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Proper user interface design is vital for both users and software engineers toward satisfaction in developing usable Web applications. Software engineers may ask users randomly, but it may lead to rework if users are not satisfied with the design of the interface once it is in the implementation stage. Thus, a more structured way to support the process of user interface design will be useful to avoid changes at a later stage. This paper adopted a systematic literature review method to gather all related works that highlight the issues and the proposed works in user interface design for Web applications. Based on the results, we can deduce the gaps from the existing works that motivate the future work in user interface design.